Colonic Polyps in Children and Adolescents - Carol A Durno (Canadian Journal of Gastroenterology)
Colonic polyps most commonly present with rectal bleeding in children. The isolated juvenile polyp is the most frequent kind of polyp identified in children. ‘Juvenile’ refers to the histological type of polyp and not the age of onset of the polyp. Adolescents and adults with multiple juvenile polyps are at a significant risk of intestinal cancer. The challenge for adult and pediatric gastroenterologists is determining the precise risk of colorectal cancer in patients with juvenile polyposis syndrome. Attenuated familial adenamatous polyposis (AFAP) can occur either by a mutation at the extreme ends of the adenomatous polyposis coli gene or by biallelic mutations in the mutY homologue (MYH) gene. The identification of MYH-associated polyposis as an autosomal recessive condition has important implications for screening and management strategies. Adult and pediatric gastroenterologists need to be aware of the underlying inheritance patterns of polyposis syndromes so that patients and their families can be adequately evaluated and managed. Colonic polyps, including isolated juvenile polyps, juvenile polyposis syndrome, FAP, AFAP and MYH-associated polyposis, are discussed in the present review.